Membrane distillation enhanced by an asymmetric electric field. Issue 6 (7th March 2014) - Du, Jennifer Runhong; Du, Wenlin; Feng, Xianshe; Zhang, Yufeng; Wu, Yimin
<x xml:space="preserve">Abstract</x> A novel membrane distillation (MD) process enhanced by an asymmetric electric field was proposed. By applying an asymmetric electric field across a membrane with an increased field intensity in the direction of permeation, the permeation of water molecules through the membrane will be facilitated by the electric potential gradient, resulting in a higher flux than that achieved with the conventional process. The effectiveness of using asymmetric electric field to enhance mass transport was confirmed experimentally, and the effects of electric field parameters (including voltage, electrode distance, and electrode geometry) on water permeation were investigated. The novel process was tested for water desalination by MD and the results showed that both permeation flux and salt rejection were increased by the electric field. © 2014 American Institute of Chemical Engineers AIChE J, 60: 2307–2313, 2014